Pengaruh Hemodialisis terhadap Fungsi Diastolik Ventrikel Kiri pada Pasien Penyakit Ginjal Kronik Stadium V - Rifqi Rahadian; Yuli Hermansyah; Yohanes Sudarmanto; Suryono Suryono (Pustaka Kesehatan, 2019)
Stage V chronic kidney disease (CKD) patients need renal replacement therapy. Hemodialysis is main choice for renal replacement therapy and correlates with changes of left ventricular function. Left ventricular diastolic function is one parameter of left ventricular function. The aim of this study was to analyze the effect of hemodialysis towards left ventricular diastolic function in stage V CKD patients at RSD dr. Soebandi Jember. This study included 30 patients (17 female, age 48,20±8,02 years) and underwent echocardiography 30 min before and after a hemodialysis session. Sample characteristics were divided into sex, age, duration of hemodialysis, blood pressure before and after hemodialysis. Diastolic function was measured with E/E’ ratio. Diastolic function criteria of 16 samples (53,5%) were normal (E/E’ ratio <10) after doing a hemodialysis session. Mean ratio E/E’ was significantly reduced (13,09±4,55 vs 11,6±5,04, p<0,05). In conclusion, hemodialysis could increase left ventricular diastolic function in stage V CKD patients at RSD dr. Soebandi Jember.